HUBUNGAN ASUPAN ENERGI DENGAN KEJADIAN STUNTING PADA BALITA USIA 12-36 BULAN DI WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM - Gultom, Yosi Melinda; Gemini, Savitri; Taluphyta, Rurry Nindya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Stunting in Indonesia is ranked third with the highest prevalence in the Southeast Asia region with a percentage (27.67%). Stunting is a growth failure with body length or height for age < -2 z-score caused by several factors, namely energy intake, birth weight, mother's education level, family income level, parenting, and food diversity. This study aims to determine the relationship between energy intake and the incidence of stunting in toddlers aged 12-36 months in the Batu Aji Health Center Working Area, Batam City in 2023. This research design uses cross-sectional. Respondents in this study were 67 toddlers. The sampling technique used was the random sampling technique. The results of the chi-square test showed (p-value = 0.001) so that H0 was rejected and Ha was accepted. So it can be concluded that there is a relationship between energy intake and the incidence of stunting in toddlers aged 12-36 months in the Batu Aji Health Center Working Area, Batam City in 2023. It is expected that health services should increase the provision of information and education to mothers of toddlers about the importance of nutrition in fulfilling energy intake in toddlers to prevent stunting, and for mothers who have toddlers to pay attention to nutritional intake and monitor the growth of toddlers by routinely coming to the Posyandu to early detect the incidence of stunting in toddlers, and for further researchers, it is hoped that this research can be used as information for research development, especially in the problem of stunting in toddlers.Keywords: Energy Intake, Toddlers, Stunting